TEACHER STRATEGIES IN ONLINE LEARNING DUE TO PANDEMIC: A LITERATURE REVIEW - Izzet Fikrotul Fauqi (JF Publisher, 2022)
Education related to how teacher teaching their students the material that help student solve the problem, increase their capability, and applied what they have learnt in their daily activities. In COVID-19 emergency, the Indonesian government issues a distance and online learning policy and students can study even in a state of social distancing. This pandemic provides a challenge for all education units to continue to provide optimal service to their students. This research aims to analyze and identify the teachers’ role in teaching and learning process that was interfere during the pandemic. This research is a qualitative research with the literature review that discusses published information in a particular subject area, and sometimes information in a particular subject area within a certain time period. This research analyzes about several articles related to the challenge that faced by teacher during online learning due to pandemic and the strategies applied by teachers as a solution to keep students motivated and well-understand about the learning material. The result of this research showed the several strategies applied by teachers during online teaching implementation, such as make interesting media and convey it via zoom, intensively motivate students and parents about the importance of online learning, uses WhatsApp groups when teaching online since many of students are familiar with WhatsApp application and combining both online chat and video conference in online teaching and learning process.